2021
DOI: 10.1177/0025802420987431
|View full text |Cite
|
Sign up to set email alerts
|

How well do Regulation 28 reports serve future public health and safety?

Abstract: Her Majesty’s (H.M.) coroners issue Regulation 28 (Reg. 28) reports following inquests. These reports concern hazards which, if mitigated, might prevent future deaths, and have addressees who are best placed to take remedial actions. Since 2013, the reports and addressees’ responses are copied to, and electronically published by, the Chief Coroner in non-exclusive demographic, aetiological or venue categories. Three of those categories were chosen so as to minimise the replication of unique cases – child death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 5 publications
4
21
0
Order By: Relevance
“… 24 This questions whether PFDs are fulfilling their purpose. Similar to Fox and Jacobson, 25 the present study found pronounced geographical variation in the issuing of PFDs and poor response rates. A review of the coronial system in England and Wales highlighted a lack of accountability, leadership, and quality assurance.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“… 24 This questions whether PFDs are fulfilling their purpose. Similar to Fox and Jacobson, 25 the present study found pronounced geographical variation in the issuing of PFDs and poor response rates. A review of the coronial system in England and Wales highlighted a lack of accountability, leadership, and quality assurance.…”
Section: Discussionsupporting
confidence: 88%
“…Our study builds on prior research that evaluated smaller samples of coroners' reports (15,16,(25)(26)(27). Compared with previous studies (26,28), we did not identify a sex imbalance.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…This questions whether PFDs are fulfilling their purpose. Similar to Fox and Jacobson [26], we found pronounced geographical variation in the issuing of PFDs and poor response rates. A review of the coronial system in England and Wales highlighted lack of accountability, leadership, and quality assurance [29].…”
Section: Comparison With Existing Literaturesupporting
confidence: 85%
“…Despite the legal requirement to respond to PFDs, there is no process for enforcing and auditing responses to ensure that necessary actions are being taken to prevent similar deaths. Others have suggested the need for sanctions to improve response rates and enforce Regulation 29 of The Coroners (Investigations) Regulations 2013 (9,37). But whether such sanctions would lead to increased actions for reducing preventable deaths has not been tested.…”
Section: Interpretation and Implications For Clinicians And Policymakersmentioning
confidence: 99%